Effects of water-aging on self-healing dental composite containing microcapsules. (April 2016) - Wu, Junling; Weir, Michael D.; Melo, Mary Anne S.; Strassler, Howard E.; Xu, Hockin H.K.
Abstract: Objectives: The objectives of this study were to develop a self-healing dental composite containing poly(urea-formaldehyde) (PUF) shells with triethylene glycol dimethacrylate (TEGDMA) and N, N -dihydroxyethyl- p -toluidine (DHEPT) as healing liquid, and to investigate the mechanical properties of the composite and its self-healing efficacy after water-aging for 6 months. Methods: PUF microspheres were synthesized encapsulating a TEGDMA–DHEPT healing liquid. Composite containing 30% of a resin matrix and 70% of glass fillers by mass was incorporated with 0%, 2.5%, 5%, 7.5% and 10% of microcapsules. A flexural test was used to measure flexural strength and elastic modulus. A single edge V-notched beam method was used to measure fracture toughness ( K IC ) and self-healing efficacy. Specimens were water-aged at 37 °C for 1 day to 6 months and then tested for self-healing. Fractured specimens were healed while being immersed in water to examine self-healing efficacy, in comparison with that in air. Results: Incorporation of up to 7.5% of microcapsules into the resin composite achieved effective self-healing, without adverse effects on the virgin mechanical properties of the composite ( p  > 0.1). An excellent self-healing efficacy of 64–77% recovery was obtained (mean ± sd; n  = 6). Six months of water-aging did not decrease the self-healing efficacy compared to 1 day ( p  > 0.1). Exposure to water did not decrease the healing efficacy, compared to that healed in air ( p  > 0.1). Conclusions: A composite was developed with excellent self-healing efficacy even while being immersed in water. The self-healing efficacy did not decrease with increasing water-aging time for 6 months. Clinical significance: The novel self-healing composite may be promising for dental applications to heal cracks, resist fracture, and increase the durability and longevity.